Existence of Solutions for the p(x)-Laplacian Problem with Singular Term. (14th March 2010) - Yongqiang, Fu; Mei, Yu
Abstract : We study the followingp ( x ) -Laplacian problem with singular term:- div   ( | ∇ u | p ( x ) - 2 ∇ u ) + | u | p ( x ) - 2 u = λ | u | α ( x ) - 2 u + f ( x, u ), x ∈ Ω, u = 0, x ∈ ∂ Ω, whereΩ ⊂ ℝ N is a bounded domain, 1 < p - ≤ p ( x ) ≤ p + < N . We obtain the existence of solutions inW 0 1, p ( x ) ( Ω ) .